Performance Assessment of Secant Pile Walls in Deep Excavations Using 3D Numerical Modeling and Monitoring Data - Indra Noer Hamdhan; Masyhur Irsyam; Agus Himawan; Sinatra Prasetyo; Rinaldi Alamsyah (Salehan Institute of Higher Education, 2026)
This study aims to evaluate the deformation behavior and internal forces of a secant pile retaining system used for deep excavation at the Sentiong Water Pump House project in North Jakarta. A three-dimensional numerical analysis was conducted using PLAXIS 3D to simulate excavation stages, groundwater conditions, and construction sequences, including secant pile installation, dewatering, strut and ground anchor installation, and structural loading. Soil parameters were derived from field and laboratory investigations and calibrated using inclinometer monitoring data. The analysis results indicate that the maximum horizontal deformation on the north side of the excavation reached 30.60 mm during the pre-stressing of the second ground anchor, which slightly exceeded the allowable limit specified in SNI 8460:2017. On the south side, the maximum horizontal deformation reached 126.3 mm during ground anchor installation, significantly exceeding the permissible deformation limit. These results demonstrate that while the secant pile system on the north side performed near the allowable threshold, the south-side retaining system exhibited insufficient stiffness and stability under combined excavation and groundwater effects. The novelty of this study lies in the integration of detailed construction-stage modeling, field monitoring calibration, and direct evaluation against national deformation criteria, providing practical insights for improving secant pile design and excavation safety in soft soil and high groundwater conditions.